La pratique de l’hypnose, de la visualisation ou de l’autohypnose par des personnes atteintes d'un cancer : une transformation de soi ? - Clémentine Raineau (Anthropologie & Santé)
Do hypnosis and relaxation practices allow for a reconfiguration of cancer care within therapeutic itineraries? From our fieldwork in Auvergne (France) with persons affected by this disease and with their therapists, we have shown that these care techniques allow the patients to acquire practical skills (autohypnosis, self-visualization and self-relaxation) and to be active in the care of their cancer, to face certain side effects of the disease and the treatments. The acquisition of these techniques of empowerment allows for the reconfiguration of the patient’s care paths vis-à-vis the “Plan Personnalisé de Soins” (Personalized Care Program) proposed by a French oncology unit. The visualization training, which comes to fruition through the discovery during the sessions of a “matrix of the imagination” anchored in the body and its exploration (through the generation and the manipulation of images), works towards metamorphosis, which tends to transform the modalities of one’s “self-in-the-world”.